1998
DOI: 10.1034/j.1399-3054.1998.1040114.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, characterization and significance of papaya β‐galactanases to cell wall modification and fruit softening during ripening

Abstract: β‐Galactosidases (EC 3.2.1.23) from ripe papaya (Carica papaya L. cv. Eksotika) fruits having galactanase activities were fractionated by a combination of cation exchange and gel‐filtration chromatography into three isoforms, viz., β‐galactosidase I, II and III. The native proteins of the respective isoforms have apparent molecular masses of 67, 67 and 55 kDa, each showing one predominant polypeptide upon SDS‐PAGE of about 31 and 33 kDa for β‐galactosidases I and III, respectively, and of 67 kDa for β‐galactos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 0 publications
3
19
0
2
Order By: Relevance
“…Numerous cell wall enzymes have been reported to catalyze this process including polygalacturonase (PG), pectin methylesterase (PME) and a-and b-galactosidases (Fischer and Bennett 1991). In papaya, even though PG and PME activities increased concomitantly with pectin solubilization and depolymerization during fruit, increased b-galactosidase activity was also observed during the last ripening stages when fruits undergo the most accelerated softening (Lazan et al 1995;Ali et al 1998). Furthermore, the wall-modifying capacity of b-galactosidase had been shown to markedly hydrolyze pectin and hemicellulose even when PG and PME were apparently not present (Lazan et al 2004).…”
Section: Introductionmentioning
confidence: 96%
“…Numerous cell wall enzymes have been reported to catalyze this process including polygalacturonase (PG), pectin methylesterase (PME) and a-and b-galactosidases (Fischer and Bennett 1991). In papaya, even though PG and PME activities increased concomitantly with pectin solubilization and depolymerization during fruit, increased b-galactosidase activity was also observed during the last ripening stages when fruits undergo the most accelerated softening (Lazan et al 1995;Ali et al 1998). Furthermore, the wall-modifying capacity of b-galactosidase had been shown to markedly hydrolyze pectin and hemicellulose even when PG and PME were apparently not present (Lazan et al 2004).…”
Section: Introductionmentioning
confidence: 96%
“…The levels of water-soluble (Zhao et al 1996;Paull et al 1999;Manrique and Lajolo 2004), chelator-soluble (Paull et al 1999;Lazan et al 1995), and alkali-soluble polyuronides have also been reported to increase during papaya fruit ripening (Zhao et al 1996;Lazan et al 1995;Ali et al 1998;Paull et al 1999). Additionally, Manrique and Lajolo (2004) have reported a loss of galactose with a simultaneous release of rhamnose during papaya ripening.…”
Section: Introductionmentioning
confidence: 85%
“…Studies on papaya cell wall have indicated that softening is accompanied by polyuronide hydrolysis and modification of hemicelluloses (Karakurt and Huber 2003;Zhao et al 1996;Paull et al 1999;Manrique and Lajolo 2004) and a continuous or temporary increase in the activities of PG (Karakurt and Huber 2003;Paull and Chen 1983), xylanase (Paull and Chen 1983) (EC 3.2.1.8), a-galactosidase (a-Gal; EC 3.2.1.22), and b-galactosidase (Ali et al 1998;Gallon et al 2009) (b-Gal; EC 3.2.1.2), and cellulase (Gallon et al 2009) (EC 3.2.1.4). The levels of water-soluble (Zhao et al 1996;Paull et al 1999;Manrique and Lajolo 2004), chelator-soluble (Paull et al 1999;Lazan et al 1995), and alkali-soluble polyuronides have also been reported to increase during papaya fruit ripening (Zhao et al 1996;Lazan et al 1995;Ali et al 1998;Paull et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous reports to show the increase in f3-galactosidase activity during fruit ripening (see Tateishi et al 2001b). There are several isoforms of f3-galactosidase and related genes in tomato (Smith and Gross 2000), but only one of them was involved in the degradation of pectin during fruit ripening of tomato (Carington and Pressy 1996), papaya (Ali et al 1998), 'D'Anjou' pear (Perdue et al 1998) and Japanese pear (Kitagawa et al 1995). mRNA level of f3-galactosidase was monitored by Northern analysis in two species of grape during ripening, and the level increased before and after veraison, when the grape suddenly soften, in one species, but not changed in the other species (Nunan et al 2001).…”
Section: Galactosidasementioning
confidence: 97%